Assessment of Phenotypic Characteristics and Work Suitability for Working Donkeys in the Central Highlands in Kenya - Mary Gichure; Joshua Onono; Raphael Wahome; Peter Gathura (Veterinary Medicine International)
The study aimed to assess the phenotypic characteristics of donkeys and their suitability for work. Data were collected on age, sex, coat color, height at withers, body length, and heart girth from 360 randomly sampled donkeys raised in a highland agroecological system in Kenya between the months of June and September 2018. Data were analyzed using descriptive statistics and ANOVA with the sex of the donkey and age group treated as sources of variation. The weight of donkeys was estimated using a formulae incorporating body length and heart girth. The study reveals that the average weight of the working donkey in the central highlands of Kenya was 155.5 kgs ± SE 1.71. Their height at withers was 99.7 cm ± SEM 0.50, with a heart girth of 113.7 cm ± SEM 0.43 and a body length of 113.2 cm ± SEM 0.58. All these body measurements varied significantly by sex and age group (P<0.001). Therefore, donkeys raised in Kenya had the same height but heavier, with longer body lengths and heart girth measurements when compared to other domesticated working donkeys in different parts of the world indicating genetic diversity, differences in ecogeographical conditions and husbandry practices. The majority (86%) of the donkeys were in good welfare conditions with moderate to ideal 86% body condition scores, minimal body lesions 5%, and lameness 18%. The results are useful for extension agents and donkey users when estimating optimal pack or cart loads in line with their welfare. The findings provide opportunities for future research on the reasons for phenotypic diversity between donkeys raised in Kenya and other parts of the world.